Isolation and Characterization of partial genomic sequence of cysteine synthase (CSase) gene from petai belalang (Leucaena leucocephala) - Athirah, Abdul Rahman. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Cysteine synthase (CSase) is an important enzyme for cysteine biosynthesis and occurred at three different organelle of plant cell such as mitochondria, cytosol and chloroplast. Petai belalang or scientifically known as Leucaena leucocephala is a leguminous plant belonging to Fabaceae family. It provides worldwide function such as feed-stock for ruminant, cropping system, charcoal and small furniture. The aim of this study was to isolate and in silico characterize the partial genomic sequence encode for cysteine synthase from L. leucocephala. Total DNA from the young leaf of petai belalang was isolated and purified by using the modified CTAB method. According to the conserved region of CSase gene from multiple alignment of mRNA sequence from five plant species; Glycine max, Solanum tuberosum, Citrullus lanatus, Arabidopsis thaliana and L. leucocephala and using L. leucocephala mRNA sequence of cysteine synthase gene as a template, the foward and reverse primers were designed. Then, the DNA fragment was amplified by using the standard polymerase chain reaction (PCR). The amplicon which was ~1,300 bp was sequenced and the sequence was edited to 372 bp. The genomic DNA showed 99 % homology with Cy-OAS-TL of L. leucocephala analyzed by BLASTn. The intron-exon regions was determined by multiple alignment and the CSase amplicon only consist of coding region. Throughout this study, the cysteine synthase sequence can be used as a foundation to understand the molecular aspect of petai belalang tree.